Multiple intracardiac tumors in a neonate. A case report - Ben David Valdés-Ramos; Carlos López-Candiani (Instituto Nacional de Pediatría, 2014)
Intracardiac tumors are uncommon in children, and to a lesser extent in newborns. Most of these tumors are rabdomiomas, which usually vary in size and number. The rabdomioma is located most of the times in the ventricles, and rarely in the atrium. The rabdomiomas can be associated with tuberous sclerosis from 56% to 86% of the cases. Nowadays, intracardiac fetal tumors can be detected through prenatal ultrasound, after the second gestation trimester. The tumor location and the hemodynamic effects will be the most important aspects that determine the severity. Serial prenatal ultrasound monitoring reveals the tumoral growth speed. It's believed that, due to an in utero maternal stimulation, an accelerated growth rate is presented during the second and third trimester, and it will slow down after the 35th week. This is a case-report of a patient with the prenatal diagnosis of an intra- cardiac mass, referred to the neonatology department of the Instituto Nacional de Pediatría.